Study on Alpha-2-macroglobulin: The New Weapon for Neuropathic Pains - C. de Castro, Jeimylo (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Alpha-2-macroglobulin’s ability to generally inhibit proteases both in chronic and neuropathic pains and inflammatory joint problems showed promise from a biological perspective. Cytokines are released as a result of nerve injury and inflammation. Axonal damage and neuropathic pains may ensue as a result of this inflammation. In a degenerative disc disease where the cartilage degradation product, the Fibronectin-Aggrecan complex (FAC) is identified, intradiscal autologous A2M injection showed clinical improvements, although further studies is needed to see consistent results. Pro-inflammatory cytokines such as IL-1, IL-6 and TNF increased during inflammation not only in the peripheral nerves but also in inflammatory joint problems, cardiovascular events and athrosclerosis event, it is interesting to note how this could be utilized to address inflammation and neuropathic pains and other inflammatory conditions.